2022
DOI: 10.1021/acsnano.2c05726
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Lasing from Two-Dimensional Homologous Ruddlesden–Popper Perovskite with Giant Nonlinear Absorption and Natural Microcavities

Abstract: Two-dimensional Ruddlesden–Popper perovskites (RPPs) with multiple quantum well-like structures, strong excitonic quantum confinement, and high stability are promising optical gain media. However, the lasing from such material with a small number of inorganic well layers is difficult to achieve. Herein, we demonstrate the low-threshold upconversion lasing from the homologous RPP (PEA)2(MA) n −1Pb n I3 n +1 (n = 2 and 3) microflakes with wavelength varies from 598 to 637 nm under 800 nm laser excitation at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Later, He et al replaced the above large organic spacer cations, BA, with PEA (Figure D) and demonstrated multiexciton lasing from n = 3 and even n = 2 single crystals at low temperatures (Figure E–G). Very recently, Gao et al further obtained two-photon pumped lasing emission from (PEA) 2 (MA) n −1 Pb n I 3 n +1 single crystals with n = 2 and 3 (Figure H–J) under 800 nm laser excitation at low temperature (≤153 K). These results together suggest that bulky organic spacer cations play an important role in determining the lasing properties of single crystalline 2D perovskites.…”
Section: Light-emitting Applications Of Osipsmentioning
confidence: 93%
See 4 more Smart Citations
“…Later, He et al replaced the above large organic spacer cations, BA, with PEA (Figure D) and demonstrated multiexciton lasing from n = 3 and even n = 2 single crystals at low temperatures (Figure E–G). Very recently, Gao et al further obtained two-photon pumped lasing emission from (PEA) 2 (MA) n −1 Pb n I 3 n +1 single crystals with n = 2 and 3 (Figure H–J) under 800 nm laser excitation at low temperature (≤153 K). These results together suggest that bulky organic spacer cations play an important role in determining the lasing properties of single crystalline 2D perovskites.…”
Section: Light-emitting Applications Of Osipsmentioning
confidence: 93%
“…(F and G) μ-PL spectra and the corresponding log–log plot of integrated emission intensity of an n = 2 (F) and 3 (G) RP perovskite flake as a function of pumped density P . (H) Lasing spectra of perovskite flakes for n = 2 (left) and n = 3 (right) at 153 and 173 K, respectively (scale bar 5 μm) . (I) Lasing threshold as a function of temperature for n = 2 (black) and n = 3 (red) flakes.…”
Section: Light-emitting Applications Of Osipsmentioning
confidence: 99%
See 3 more Smart Citations